Design and manufacture the inner shell of diesel furnace - Muhammad Muizzuddin, Yusof (2010)
This report is about the design and manufactures the inner shell of diesel furnace. This project encourages the study of melting furnace. Melting furnace is a device used to melt the metal for casting metal application. The project is start with the study and research. From the information gathered from literature study, four designs had been created. One of the designs is chosen using screening concept and final design is decided. The fabrication process consists of cutting process and construction of the wall inside the furnace. By putting the buffers will keep the heat inside the furnace and make the crucible melt the metal faster. Furthermore, the furnace is heat up by the burning of diesel fuel to blow the fire into the combustion chamber. When the product is finished, it is tested to determine the time of metal to melt completely and to prove the product is working and success. All of the problems faced during and after making the product are discussed. Some recommendation base on the problems also discussed in the last chapter of this report to improve the product in the future.